Militerisasi Agrikultur: Keterlibatan Militer Dalam Program Food Estate Indonesia 2020-2024 - Wildan Faisol; Heri Herdiawanto; Ashabriel Nadiva Candialmeera; Nobel Jihadine; Muhamad Arif (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2025)
The COVID-19 pandemic triggered global food security threats, prompting the Indonesian government to launch the Food Estate as a National Strategic Project. A defining feature of this policy is the active involvement of the military, with the Ministry of Defence appointed as the leading sector. This study analyzes the factors and implications of military involvement in food governance (2020–2024) through Donald Travis’s Pragmatic Civil Control theory. Findings indicate that the government utilized the pandemic as a